Gojek Accelerate Economic Recovery through the Digitalization of MSMEs in Makassar - Karim, Abdul; Asrianto, Asrianto; Ruslan, Muhlis; Said, Miah (Bina Nusantara University, 2023)
It was a qualitative descriptive research to determine the role of the digital economy in Makassar City’s economic growth. Data were collected from some websites in Indonesia, and analysed by using NVivo 10 software. The results indicate the acceleration of the digital transformation of MSMEs in Makassar City could not be separated from the support of digital platforms. Before the pandemic, the digital economy, namely Gojek, contributed to economic growth. Makassar City's economy has experienced an increase in MSME turnover registered on social sellers GoFood, GoPay, and GoSend. The digital economy plays a vital role in driving the wheels of the Makassar City economy. In 2021, Gojek and GoTo Financial were estimated to contribute around IDR 4,6 trillion, or 3% of Makassar City's Gross Regional Domestic Product (GRDP). Since data reveals that Gojek Food is encouraging, Gojek is also accelerating digitization and financial inclusion for MSMEs. MSMEs are going digital for the first time (87%) and are using non-cash payments (51%). 37% of GoRide partners and 22% of GoCar partners have saved regularly since joining Gojek. According to estimates, the Gojek ecosystem contributes IDR 249 trillion, or 1,6% of Indonesia’s GDP—resilience and recovery speed through increased revenue, mainly for MSMEs in the Gojek ecosystem. During the pandemic, consumer loyalty aided economic recovery at the national and regional levels.